A Lewis base and boundary passivation bifunctional additive for high performance lead-free layered-perovskite transistors and phototransistors. (September 2021) - Zhu, H.; Liu, A.; Zou, T.; Jung, H.; Heo, S.; Noh, Y.-Y.
Abstract: Halide perovskite semiconductors exhibit a low intrinsic effective mass of charge carriers; however, their development of transistors is lagging far behind the development of photovoltaic and light-emitting diodes. In this study, we report highly reproducible phenethylammonium tin iodide transistors with mobility over 4 cm 2  V −1  s −1 and an on/off ratio over 10 5 using a simple method of adding a bifunctional additive, urea, into the precursor. This non-volatile Lewis base can modify the crystallization speed and passivate grain-boundary defects, enabling a significant improvement in the transistor characteristics over pristine devices without urea. Furthermore, we demonstrate unprecedented phototransistor characteristics, with detectivity exceeding 10 17 Jones when the improved perovskite transistors are used. It is expected that more intensive efforts can be attracted to advance the development of high-performance perovskite (photo)transistors. Graphical abstract: Image 1 Highlights: Perovskite transistors have high intrinsic mobility but with less study attention. Highly reproducible phenethylammonium tin iodide transistors were reported. A Lewis base and boundary passivation bifunctional additive urea was utilized. The transistors show mobility over 4 cm 2  V −1  s −1 and on/off ratio over 10 5 . The transistors also show high photo detectivity over 10 17 Jones.